The Knowledge and Awareness on Polycystic Ovarian Syndrome among Lady Health Visitors in Public Health Nursing School Lahore: Knowledge and Awareness on PCOSs - Kiran, Saba; Sarwar, Hajra; Masih, Sarfraz (Pakistan Journal of Health Sciences, 2023)
Polycystic Ovarian Syndrome is a common endocrine condition, rises in adolescent girls and young women during their reproductive years. According to the World Health Organization (WHO), 116 million (3.4%) of women worldwide experienced PCOS in 2012. PCOS increases a woman’s risk of type 2 diabetes, cardiovascular disease, infertility, anxiety, and depression, as well as a poor quality of life related to their health. Objectives: To assess the knowledge and awareness on polycystic ovarian syndrome among lady health visitors in Public Health Nursing School Lahore. Methods: A Descriptive Cross-Sectional study was conducted at Public Health Nursing School in Lahore. A total of 141 participants were recruited through random sampling technique. Lady health visitor (LHV) students of first year and second year between the age group 17 to 30 year were participated in the study. Data analysis was done using SPSS version-25, the most recent release of the Statistical Package for Social Sciences (SPSS). Results: Results of the study indicated that majority of participants 114 (80.9 %) were of age ranging from 17-20 years and belongs to belongs to urban areas 75(53.2%). The findings revealed that data was normally distributed as p-value is < 0.05. Results indicated that the total knowledge score of participants regarding PCOS was poor. Conclusions: It was shown that the participants knew nothing about PCOS. The participants’ understanding of PCOS risk factors, factors connected to PCOS, and consequences from PCOS is noticeably lacking. A successful teaching intervention designed specifically for nurses can greatly improve their understanding of PCOS.